Analysis of Life-Saving Facilities System and Fire Management Facilities at Ogan Ilir Police Station in 2020 - Vira Nalia Maharani; Novrikasari Novrikasari; Desheila Andarini; Anita Camelia; Poppy Fujianti (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Fire cases in Indonesia continue to increase every year. Based on data from the Regional Disaster Management Agency (BPBD) of South Sumatra, there were 116 cases of fires during 2019 in South Sumatra. An office building is a building that serves as a place for people to do office activities. Office buildings that have been relatively safeare actually faced with various risks of emergency hazards such as fires, earthquakes, floods and others. Ogan Ilir Police Station has experienced a life-threatening fire and losses, and therefore life facilities are needed according to the existing SNI. The purpose of this study is to analyze life-saving facilities and fire management facilities in Ogan Ilir Police Station, South Sumatera. Methods: This research used a qualitative descriptive method. Descriptive research was conducted by evaluating the fire protection system in accordance with the national standard in reference to the Regulation of the Minister of Public Works. Sources of information were obtained from key informants and other informants. Results: The suitability of the fire protection system at Ogan Ilir Police Station with the standards of the Minister of Public Works No. 26/PRT/M/2008 for the system of life-saving has complied with the requirements. Meanwhile, fire fighting facilities such as fire extinguishers have been installed, but there are some small elements that are not in accordance with the requirements. Conclusion: The fire protection system at Ogan Ilir Police Station, South Sumatera has not complied with the requirements of the Minister of Public Works No. 26/PRT/M/2008.